Patient safety tool kit - World Health Organisation (World Health Organisation, 2021)
Patient safety is considered a priority for health systems worldwide. In the WHO Eastern Mediterranean Region, available data show that, on average, health care-related harmful incidents affect 8 in 100 patients, and 4 out of 5 incidents are preventable. In 2011, the WHO Regional Office for the Eastern Mediterranean published the Patient safety assessment manual as part of the WHO patient safety friendly hospital initiative. It aims to assess the level of compliance against a set of evidence-based standards covering the various domains of patient safety at the hospital level. Since the manual was published efforts have been made by local teams for the expansion and ownership of this initiative as a tool that enables them to understand and assess the level of safety in their health care institutions. A second edition of the manual is currently in preparation. This new publication, Patient safety tool kit, builds on the growing regional need to develop the capacities of health professionals with regard to developing a patient safety improvement programme at the operational level and implementing corrective measures, adapted to local settings. Universal health coverage has been proposed as a goal for health in the next round of global development priorities post-2015. The bottom line is that simply expanding access will not be enough unless we simultaneously ensure that the care provided is of sufficiently high quality, where safety should be one of its core dimensions. Improving patient safety and reducing the burden of unsafe care must continue to be an important priority for all the health care systems in the Region. I encourage ministries of health, as well as academic institutions and professional associations to own and make use of the Patient safety tool kit.